High-precision U-Pb calibration of Carboniferous glaciation and climate history, Paganzo Group, NW Argentina - Gulbranson, Erik L. (2010)
The duration and geographic extent of Carboniferous glacial events in southern Gondwana remain poorly constrained despite recent evidence for a more dynamic glacial history than previously considered. We report 10 high-precision (2σ ± <0.1%) U-Pb ages for the Permian-Carboniferous Paganzo Group, NW Argentina, that redefine the chronostratigraphy of the late Paleozoic Paganzo and Río Blanco Basins, and significantly refine the timing of glacial events and climate shifts in the western region of southern Gondwana. Radiometric calibration of the Paganzo Group indicates three pulses of Carboniferous glaciation in the mid-Visean, the late Serpukhovian to earliest Bashkirian, and between the latest Bashkirian to early Moscovian. An abrupt shift in depositional style from high-sinuosity single-storied fluvial deposits and clay-rich paleosols to low-sinuosity multistoried feldspathic fluvial deposits intercalated with eolianites and calcic paleosols is constrained to the latest Moscovian and earliest Kasimovian. These constraints indicate a relatively abrupt climate shift from humid-subhumid to nonseasonal semiarid regional climate conditions that occurred significantly earlier than previously inferred (Early Permian). This period of high-latitude aridity was contemporaneous with a shift to dryland depositional environments and a major vegetation regime shift documented throughout the Pangean paleotropics in the Pennsylvanian.